Analisis efek Islamic marketing mix terhadap volume penjualan pada Warung Makan Dapur M’riah Mojokerto - Mokhammad Ainurrofiq (FADZAT: Jurnal Ekonomi Syariah, 2022)
The research objectives are as follows: 1) To simultaneously analyze the effect of product, price, promotion and distribution on sales volume. 2) To partially analyze the effect of product, price, promotion and distribution on sales volume. 3) Analyze the main factors that are the most dominant product, price, promotion and distribution to increase sales volume. The population in this study was the unknown population, the degree was 1.96 with an error rate of 5%, a sample of 96 respondents was determined by sampling using incidental sampling. Validity is measured by product moment correlation, reliability is measured by consistency of alpha reliability intervals. The classical assumption test consists of five tests, namely the normality test, autocorrelation test, heteroscedasticity test, multicolinearity test and linearity test. To prove the hypothesis formulated in this study, the F test and t test were used. From the research results, it can be concluded that: 1) Product, price, promotion, and distribution simultaneously influence sales volume. 2) Product has a partially significant effect on Sales Volume, Price has a partially significant effect on Sales Volume, promotion has a partially significant effect on Sales Volume, distribution has a significant negative effect on the Sales Volume variable. 3) Promotion has a dominant effect on Sales Volume.